Effect of Risk Alleles in CFH, C3, and VEGFA on the Response to Intravitreal Bevacizumab in Tunisian Patients with Neovascular Age-related Macular Degeneration - Habibi, I.; Kort, F.; Sfar, I.; Chebil, A.; Bouraoui, R.; Ben Abdallah, T.; Gorgi, Y.; El Matri, L. (Klinische Monatsblätter für Augenheilkunde, 2016)
Purpose. The aim of this pharmacogenetic study was to evaluate the impact of high-risk alleles in factor H, factor C3 and vascular endothelial growth factor (VEGF) on the response to intravitreal bevacizumab in patients with neovascular age-related macular degeneration (AMD) in a Tunisian population.Methods. Ninety patients with active neovascular AMD treated with intravitreal bevacizumab injections were enrolled in the study. Treatment response was evaluated by comparing BCVA at baseline and at 12 months. Patients were classified into either “poor responders” (PR) or “good responders” (GR). Single nucleotide polymorphism (SNP) genotyping was performed for rs1061170 in FH, rs2230199 in C3 andrs699947, rs2010963 and rs3025039 in VEGF. The association between genotype and visual response at 12 months was assessed.Results. Seventy-seven participants were assigned to the GR group and 13 to the PR group. No correlation was found between FH, C3 and VEGF variant alleles and treatment response. However, haplotype analysis of rs699947 ((− 2578) C/A), rs2010963 ((+ 405) C/G) and rs3025039 ((+ 936) C/T) SNPs revealed that the AGT haplotype was associated with a poor response at 12months (p = 0.048). No association was found between treatment response and the cumulative effect of all high-risk alleles of C3, FH and VEGF. All three types of CNV were found in both groups at a comparable frequency.Conclusions. The VEGF haplotype TGA could be used as a marker for poor visual prognosis in Tunisian patients with neovascular AMD treated with bevacizumab.
Keywords: AMD; factor H; VEGF; C3; anti-VEGF therapy